Sistemas de escores clínicos para diagnóstico de trombocitopenia induzida por heparina - Daniela Rezende Garcia Junqueira (2008)
Within the adverse reactions to the anticoagulant heparin, heparin-induced thrombocytopenia (HIT) is a dangerous and usual hematological adverse reaction. Its most important consequence is the paradoxal increase in the risk of thromboembolic complications, this being able to be increased up to 75 %. The early detection of the reaction and the immediately introduction of adequate treatment may overcome this serious clinical condition. The thrombocytopenic condition of HIT is due to the platelet activation induced by heparindependents antibodies. The diagnosis relies on monitoring platelets count and on theinvestigation of existing antibodies in the patients serum or of the activation of the platelets induced by these antibodies. Thrombocytopenia is the main signal of the adverse reaction and laboratorial tests constitute the golden-pattern diagnosis for HIT. Clinical Score Systems (CSS) have been developed to evaluate HIT considering only the clinical symptoms ofsuspect cases. This study aimed to determinate the reliability and accuracy of two CSS described in literature in comparison to golden-pattern diagnosis, as well as to propose a new system to HIT diagnosis. For this, it was used a group of 73 clinical cases extracted from the literature to which the system was applied. The determination of reliability and accuracy was made by means of kappas coefficient and measures of sensibility and specificity. The analysis showed that previous CSS agrees from regular to poor with the results of laboratorialtests. The proposed CSS, even with a few advantages, did not reach the ideal concordance level. The accuracy evaluation showed that, in a general way, these systems need to be improved in means of sensibility and specificity. The results demonstrate that it is still necessary to upgrade the construction of these instruments using tools as from statistics multivariate analysis. Keywords: heparin-induced thrombocytopenia; clinical score systems; concordance; reliability, accuracy.